Chondroinduction of Mesenchymal Stem Cells on Cellulose-Silk Composite Nanofibrous Substrates: The Role of Substrate Elasticity - Begum, Runa; Perriman, Adam W.; Su, Bo; Scarpa, Fabrizio; Kafienah, Wael (Frontiers in Bioengineering and Biotechnology, 2020)
Smart biomaterials with an inherent capacity to elicit specific behaviors in lieu of biological prompts would be advantageous for regenerative medicine applications. In this work, we employ an electrospinning technique to model the in vivo nanofibrous extracellular matrix (ECM) of cartilage using a chondroinductive cellulose and silk polymer blend (75:25 ratio). This natural polymer composite is directly electrospun for the first time, into nanofibers without post-spun treatment, using a trifluoroacetic acid and acetic acid cosolvent system. Biocompatibility of the composite nanofibres with human mesenchymal stem cells (hMSCs) is demonstrated and its inherent capacity to direct chondrogenic stem cell differentiation, in the absence of stimulating growth factors, is confirmed. This chondrogenic stimulation could be countered biochemically using fibroblast growth factor-2, a growth factor used to enhance the proliferation of hMSCs. Furthermore, the potential mechanisms driving this chondroinduction at the cell-biomaterial interface is investigated. Composite substrates are fabricated as two-dimensional film surfaces and cultured with hMSCs in the presence of chemicals that interfere with their biochemical and mechanical signaling pathways. Preventing substrate surface elasticity transmission resulted in a significant downregulation of chondrogenic gene expression. Interference with the classical chondrogenic Smad2/3 phosphorylation pathway did not impact chondrogenesis. The results highlight the importance of substrate mechanical elasticity on hMSCs chondroinduction and its independence to known chondrogenic biochemical pathways. The newly fabricated scaffolds provide the foundation for designing a robust, self-inductive, and cost-effective biomimetic biomaterial for cartilage tissue engineering.